Inspection and certification manual for cassava planting material in Uganda - Ministry of Agriculture, Animal Industry and Fisheries, Uganda (2024)
The National Seed Certification Services (NSCS), Department of Crop Protection, Ministry of Agriculture, Animal Industry, and Fisheries (MAAIF) has designated inspectors of cassava planting material (seed) to use this handbook. The inspectors will guarantee that the produced cassava seed satisfies the necessary requirements. It will also be utilized by seed growers, training facilities, and cassava seed merchants (business owners), for whom a formal certificate attests to the quality of the seed produced. For cassava seed to be eligible for certification, the handbook outlines the minimal requirements that must be fulfilled in the tissue culture lab, screen house, and fields. Land requirements, isolation distances, degrees of disease and pest tolerance, and seed standards are some of the requirements documented here for ensuring compliance for quality seed production in the country